The myth of the Renaissance in nineteenth-century writing - Bullen, J. B. (Clarendon, 1994)
This work traces the genesis and development of the concept of the Renaissance in the literary, religious, political, and critical writing of the late-18th and 19th centuries. Among the authors discussed in this book are Voltaire, Ruskin, Browning, George Eliot, Swinburne, Arnold and Pater.
10.1093/acprof:oso/9780198128885.001.0001
Keywords: English literature; Renaissance in literature; French literature; Renaissance; Myth in literature; Romanticism